Biocontrol of slugs: Effects of slug parasitic nematodes and bacterial metabolites on harmful slugs - Weijler, Victoria (Jihočeská univerzita, 2023)
The effects of combining secondary metabolites produced by Xenorhabdus bacteria with slug parasitic nematodes belonging to the genus Phasmarhabditis on the pestiferous slug species Arion vulgaris were investigated. Secondary metabolites from ten different Xenorhabdus strains were tested and their slug repellent effects as well as their impact on the slugs' feeding behavior were observed.
Biocontrol of slugs: Effects of slug parasitic nematodes and bacterial metabolites on harmful slugs
Keywords: Biological control; Phasmarhabditis bohemica; Phasmarhabditis apuliae; Phasmarhabditis hermaphrodita; Xenorhabdus; Arion vulgaris; Biological control; Phasmarhabditis bohemica; Phasmarhabditis apuliae; Phasmarhabditis hermaphrodita; Xenorhabdus; Arion vulgaris